Short-term Surgical Outcomes after Laparoscopic Excision of Choledochal Cyst and Roux-en-Y Hepaticojejunostomy in Children - Keerthika Murali; Anjan K. Dhua; Vishesh Jain; Devendra K. Yadav; Prabudh Goel; Sandeep Agarwala; Rakesh Kumar; Devasenathipathy Kandasamy; Monikha Potturu (Journal of Indian Association of Pediatric Surgeons)
Background: Despite being a technically demanding procedure, the laparoscopic approach for choledochal cyst excision (LEC) has gained popularity in the last two decades. We conducted a study to evaluate the outcomes of the initial cohort of LEC and Roux-en-Y hepaticojejunostomy performed at our center. Subjects and Methods: A retrospective observational study was conducted. Medical records of patients who underwent LEC from July 2019 to April 2023 at our institute were retrieved and analyzed. Results: Twenty-eight patients were included in our study, of which 68% (n = 19) were females. The median age of the cohort was 5.5 years. 26/28 patients (92.8%) were diagnosed with Type 1 Choledochal cyst (CC), and Type 4a CC was noted in two children (7.2%). Majority of our patients were symptomatic. Pain in the abdomen was the predominant symptom noted in 26/28 patients (93%), eight children (28.5%) presented with jaundice. Antenatal diagnosis of choledochal cyst (CC) was established in one child (3%). Anomalous pancreaticobiliary junction was noted in 10/28 patients (35%) on magnetic resonance cholangiopancreatography. Clavien–Dindo Grade 3A and 3B complications were noted in 7% of patients each, Grade 1 in 17.5%, and Grade 2 in 3.5%. The overall morbidity rate was 28%, and there was no mortality. No cases of malignancy were reported. On a 3-month follow-up, 27/28 patients (96.5%) underwent hepatobiliary iminodiacetic acid scan, which showed good tracer clearance. Conclusions: Laparoscopic excision of CC in 28 pediatric patients demonstrated safety and efficacy. The average surgery duration was 240 min, with a low conversion rate to open surgery (3.5%). The study confirms that laparoscopic approach as a viable option, although it requires an experienced surgical team.